INTERNATIONAL TRADE, R&D SPILLOVERS AND PRODUCTIVITY: EVIDENCE FROM INDIAN MANUFACTURING INDUSTRY - M. Parameswaran (Centre for Development Studies-WP385, 2007)
This paper examines the effect of trade facilitated R&D spillovers on the productivity of manufacturing firms in India. Though developing countries are considered as the major beneficiaries of trade facilitated R&D spillovers, detailed empirical investigations in their context are lacking. The paper distinguishes R&D spillovers into two types and examines their effect on productivity. It also considers the intersectoral variation in productivity effect and the importance of firms' investment in R&D, imported technology and plant and machinery in enhancing the effect on productivity. The paper uses firm level panel data and an improved estimation method. It shows that R&D spillovers have a significant effect on productivity and there exists intersectoral variation with greater contribution to productivity in technology intensive industries. The paper also shows that firms' investment in R&D and plant and machinery are enhancing the productivity effect of R&D spillovers